Use of a Prenylation Inhibitor as a Novel Antiviral Agent - Glenn, Jeffrey S. (American Society for Microbiology, 1998)
No specific therapy exists for hepatitis delta virus (HDV), which can cause severe liver disease. Molecular genetic studies have implicated the prenylation site of large delta antigen as a critical determinant of HDV particle assembly. We have established a cell culture model which produces HDV-like particles, and we show that delta antigen prenylation can be pharmacologically inhibited by the prenylation inhibitor BZA-5B. Furthermore, BZA-5B specifically abolishes particle production in a dose-dependent manner. These results demonstrate that the use of such a prenylation inhibitor-based antiviral therapy may be feasible and identify a novel class of potential antiviral agents.